Phytoplankton as trophic descriptors of a series of Mediterranean reservoirs (Catalonia, Spain) - Moschini-Carlos, Viviane [UNESP]; Pompêo, Marcelo; Nishimura, Paula Yuri; Armengol, Joan (Schweizerbart, 2017)
The aim of this work was to determine the ways in which the associations of phytoplankton (species, classes, and functional groups) responded to different trophic states in a series of Mediterranean reservoirs (La Llosa del Caval, Sant Ponç, La Baells, Santa Fe, Susqueda, Sau, and Foix). The results showed that the average trophic state index increased from the reservoirs with lower trophic states (La Llosa, Sant Ponç, and La Baells) to those with higher trophic states (Santa Fe, Susqueda, Sau, and Foix). The structure of the phytoplankton community followed the trophic gradients of these reservoirs. Differences in illumination, nutrient supply, and mixing regime were the determining factors of this pattern, and were reflected in the functional groups found. In the La Llosa, San Ponç, and La Baells reservoirs, oligotrophic conditions, extensive euphotic zones, and deficiency of phosphorus were associated with small flagellated mixotrophic organisms belonging to the Lo, E, X2, X3, A, and R functional groups. The Susqueda and Sau reservoirs were classified as mesotrophic and eutrophic, respectively, and were mainly dominated by small organisms tolerant to deficiency of light and nutrients (phosphorus), represented by the functional groups B, A, H1, X1, MP, N, J, S1, Y, and Lo. The hypereutrophic Foix reservoir, characterized by nutrient-rich conditions with high concentrations of organic matter, was dominated by large organisms tolerant to light deficiency and high turbidity, represented by codons Y, H1, and W2. In the Santa Fe reservoir, there was a predominance of algae represented by functional groups W2 and C, which were adapted to light deficiency, slightly acidic pH, and high levels of nutrients such as phosphorus and silicate. It could be concluded that for these ecosystems, classification according to the Q-Index index corresponded to classification using the trophic state index (TSI), with the reservoirs classified as oligotrophic and mesotrophic being considered to have Good and High ecological status, respectively, while the eutrophic and hypereutrophic reservoirs showed Tolerable and Medium conditions, respectively. From exploratory analyses, conducted using the environmental variables and the composition of the phytoplankton community, considering the descriptor species, classes and functional groups, it appeared that all of the parameters could explain the community. Nonetheless, this research confirmed the potential use of phytoplankton functional groups, since they can provide information on the ecology, functional traits, and tolerances of the species, characterizing the trophic states of the reservoirs.
Keywords: Functional groups; Phytoplankton; Reservoir; Trophic status